2021
DOI: 10.1038/s41366-021-00868-5
|View full text |Cite
|
Sign up to set email alerts
|

Are adipokines the missing link between obesity, immune response, and outcomes in severe COVID-19?

Abstract: Introduction Obesity is commonly reported in COVID-19 patients and is associated with poorer outcomes. It is suggested that leptin could be the missing link between obesity and severe COVID-19. Our study aimed to unravel the link between adipokines, COVID-19 status, immune response, and outcomes in severe pneumonia. Methods In this prospective observational single-center study, 63 immunocompetent patients with severe pneumonia (36 non-COVID-19 and 27 COVID-19) were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
6
25
0
Order By: Relevance
“…It is well established that adipose tissue is a major source of adipokines (adiponectin, leptin) and proinflammatory mediators (monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor (TNF-a), factor D, IL-6), which mitigate a long-lasting low-grade inflammation and prothrombotic conditions that are exacerbated in the context of SARS-CoV-2 infection, predisposing to cardio-respiratory failure (reviewed in (12,13)). Indeed, adiponectin circulating levels were shown to be significantly reduced in patients with COVID-19 respiratory failure in multiple studies (14)(15)(16). Moreover, leptin, which serum levels largely depend on the total adipose mass, also provides a high impact on the immune system, as it favors monocytes/macrophages activation, proinflammatory cytokines release and a predominant Th-1 response, the three hallmarks of immune responses noticed in critical COVID-19 patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that adipose tissue is a major source of adipokines (adiponectin, leptin) and proinflammatory mediators (monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor (TNF-a), factor D, IL-6), which mitigate a long-lasting low-grade inflammation and prothrombotic conditions that are exacerbated in the context of SARS-CoV-2 infection, predisposing to cardio-respiratory failure (reviewed in (12,13)). Indeed, adiponectin circulating levels were shown to be significantly reduced in patients with COVID-19 respiratory failure in multiple studies (14)(15)(16). Moreover, leptin, which serum levels largely depend on the total adipose mass, also provides a high impact on the immune system, as it favors monocytes/macrophages activation, proinflammatory cytokines release and a predominant Th-1 response, the three hallmarks of immune responses noticed in critical COVID-19 patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, adiponectin circulating levels were shown to be significantly reduced in patients with COVID-19 respiratory failure in multiple studies (14)(15)(16). Moreover, leptin, which serum levels largely depend on the total adipose mass, also provides a high impact on the immune system, as it favors monocytes/macrophages activation, proinflammatory cytokines release and a predominant Th-1 response, the three hallmarks of immune responses noticed in critical COVID-19 patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma levels of APN/Lep were correlated with glucose metabolism and BMI (insulinemia and glycemia), being scarcely distinct between the two sets that were evaluated. Adipokines were not linked with the majority of the various inflammatory proteins, duration of mechanical ventilation, or initial severity (SOFA score), although Lep concentrations were inversely linked with IL-1 and IL-6 ( Blot et al, 2021 ).…”
Section: Role Of Apn In Sars-cov-2 Infectionmentioning
confidence: 95%
“…Not all studies have found a significant correlation between adipokine levels with most inflammatory mediators and the severity of the disease [46] . Plasma cytokine levels between patients with or without obesity found significant differences only in the baseline IL-1β levels, which were lower in metabolic syndrome (MeS) than non-MeS patients, with a specific cytokine pattern having been identified that correlated with mechanical ventilation [47] .…”
Section: Impact Of Covid-19 On the Immune Response Of Patients With O...mentioning
confidence: 98%